FORMATION OF THE LABOR POTENTIAL OF RURAL TERRITORIES AND WAYS OF ITS EFFECTIVE USE (Journal of Universal Science Research, 2025)
In this article, the study of labor potential reveals its content and essence in a resource style, both qualitative and quantitative. The formation of the labor potential of the village as a socio-economic category, its research and study have gone through several stages. As a result of the development of socio-economic relations, the meaning and content of such economic concepts and categories as "labor force", "labor resources", "labor potential" also changes somewhat. These concepts have become widely used not only in the scientific and economic literature, but also in our daily practice. In the economic literature, there are still different views on the concept of the labor potential of society, and these concepts remain the subject of controversy due to the need to differentiate from it the concepts of "labor resources" and "labor force" related to this concept.